Development of time delay voltage control for lead acid battery using arduino - Mohammad, Nurul Nadia (2014)
A time delay controller with voltage control technique is designed and developed in this project. In order to control the output voltage, a DC-DC buckboost converter has been development. The buckboost circuit with mosfet as a switching component has been drives by using gate driver as a medium between buckboost circuit and the ARDUINO that generates the PWM signals. The several of input voltage range which is from 10V for minimum voltage until 18V for maximum voltage has been tested in this project to determine the effectiveness of the output results for charging a battery. Finally, the control performance was evaluated through both simulations by using MATLAB software and also the experimental hardware. The results are observed in three conditions which are simulation, open loop control and close loop control. The simulation and experimental hardware results indicate that this control method shows successful for charging a battery.